Selective Vicinal Diiodination of Polycyclic Aromatic Hydrocarbons. Issue 36 (3rd September 2020) - Kaehler, Tanja; John, Alexandra; Jin, Tao; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract : Vicinally diiodinated polycyclic aromatic hydrocarbons (I2 ‐PAHs) are accessible from the corresponding diborylated B2 ‐PAHs through boron/iodine exchange. The B2 ‐PAHs have been prepared via twofold electrophilic borylation reactions templated by a vicinally disilylated benzene. Our protocol is applicable to fluorenes, acenes, annulated acenes, oligoaryls, and even [5]helicene. Using B2 ‐naphthalene as the example, we have shown that the reaction scope can, in principle, be expanded to include the synthesis of vicinally dibrominated and dihydroxylated PAHs. The usefulness of the building blocks provided by our method in the field of optoelectronic materials was demonstrated by the successful conversion of I2 ‐fluoranthene to the analogous doubly alkynylated fluoranthene emitter. Abstract : The magic I – versatile and so far elusive vicinally diiodinated PAHs have been prepared via a sequence of electrophilic borylation and boron/iodine exchange reactions.